Potency of fiber rumen bacterial isolates from local buffalo inoculated into Frisian Holstein calves during preweaning period - Iwan Prihantoro; D Evvyernie; Suryani .; L Abdullah; N.S Yunitasari; A.P Sari; D Khairunisa; A Haziq; N Rahayu; T Toharmat (Indonesian Center for Animal Research and Development (ICARD), 2012)
Fiber-digesting bacteria are the main rumen bacteria that play an important role in digesting feed. These bacteria are adapted to low quality forage from agricultural byproduct. The aim of these study was to determine the potency of fiber-digesting bacteria consortium obtained from buffalo rumen inoculated to Frisian Holstein calves during preweaning on feed consumption, utilization, mineral uptake and physiological status. This study used 14 isolates of bacteria obtained from collection of Faculty of Animal Science, Bogor Agricultural University. The experimental unit consisted of six Frisian Holstein calves at two week old with the average body weight of 38.00 ± 6.23 kg. Calves were inoculated by 20 ml of fiber-digesting rumen bacterial isolates [4.56 x 109 cfu/ml] every morning for four weeks. Experimental design used was based on a completly randomized design with three calves received the respective inoculation (treatment group) and three calves without any inoculation (control group). Data were analyzed statistically using t-test method with α = 0.05 and 0.01. The results showed that fiber-digesting bacteria (FDB) from rumen buffalo have adapted in the calves rumen since preweaning periode. Inoculation FDB increased the number of rumen bacteria, digestibility of protein and P uptake calves at eight weeks old. Increased feed intake, uptake of Mg and cobalt calves at 14 weeks old. Without causing any negative effects on ADG, physiological status and rumen fermentability. Key Words: Fiber-Digesting Bacteria, Nutrient Intake, Rumen Fermentability